A Sine Waveform Generator for On-Chip Testing of the Audio Chip - Li, Hongzhi; Eckmüller, Josef; Sattler, Sebastian; Eichfeld, Herbert (ANALOG 2003, 2003)
A sine waveform signal generator for the on chip testing of mixed-signal circuits for speech processing is present. The idea behind is to attenuate the higher requencies in a periodic triangular waveform. The hardware implementation is discussed. And the simulation results validate our proposal. This generator can be employed for both the digital BIST and the analog/mixed-signal BIST applications with a verified DAC together.
elib2cris::1512001600,li2003c